On the taxonomic status of Ichthyophis husaini Pillai & Ravichandran, 1999 (Amphibia: Gymnophiona: Ichthyophiidae) - Kamei, Rachunliu G.; Biju, S. D. (Zootaxa, 2016)
Extensive surveys at and around the type locality of Ichthyophis husaini Pillai & Ravichandran, 1999 (an ‘unstriped’ Ichthyophis) in North East India between 2008 and 2014 yielded tens of striped but no unstriped specimens of Ichthyophis. Contrary to the original description, we observed a lateral stripe on the holotype of I. husaini. The holotype of I. husaini is very similar to the holotype of the striped species I. garoensis Pillai & Ravichandran, 1999, which was collected from a locality only 20 km away from the type locality of I. husaini. The holotypes of these two species are also very similar to 12 newly collected specimens of striped Ichthyophis from this area. We conclude that the holotypes of I. husaini and I. garoensis represent but a single species, and we designate Ichthyophis husaini Pillai & Ravichandran, 1999 as a junior subjective synonym of Ichthyophis garoensis Pillai & Ravichandran, 1999. This taxonomic action and newly reported material extends the known geographic range of I. garoensis. It also reduces the number of Ichthyophis species of North East India to eight, and restricts unstriped members of the genus within this region to a single species (I. sikkimensis Taylor, 1960) that is known only from the far west of the region.